The future of the high educational inspection: an unfinished situation - Esteban Frades, Santiago (Avances en Supervisión Educativa, 2019)
The purpose of this work is to publicize the task of high educational inspection from different points of view, taking into account the relevance that has acquired in the media for the political events that are living in Spain, above all, with the Catalan question. In the legal configuration a historical tour of the High Inspection is made from the constitutional mandate of 1978 until the configuration in the Organic Law 2/2006 of Education of May 3, going through the definition in the respective Statutes of the Autonomous Communities and the Royal decrees that have been shaping their organization and functions. It is explained how the competences of the High Inspection have been evolving and the importance of the interpretation that the Constitutional Court has made in different judgments on what its role of verification, verification or verification of the basic regulations of the State in educational matter. An analysis is made of the procedures used by this institution to carry out its work, as well as the main tasks it carries out, its organic and functional dependence, as well as the analysis compared with other high state inspections.
Keywords: High inspection; education; Constitutional Court; Constitution 1978; competences; organic dependence; State; organization; procedures.